HPLC-MS method development and validation for simultaneous quantitation of GZK-111 and CPG compounds in rat plasma - A. L. Podolko; P. O. Bochkov; G. B. Kolyvanov; A. A. Litvin; O. G. Gribakina; R. V. Shevchenko; V. P. Zherdev (LLC "Publisher OKI", 2020)
The technique of quantitative determination of GZK-111 and CPG compounds in rat blood plasma has been developed. The analysis was carried out using the combined method of high-performance liquid chromatography with mass spectrometric detection. The method was linear in the concentration range of 25-1000 ng/ml for both compounds. Percentage of GZK-111 extraction from rat blood plasma was 57.8 %. The lower limit of detection for GZK- 111 compound was 25 ng/ml. Percentage of extraction of CPG compound was 42.5 %. The lower limit of detection of CPG compound was also 25 ng/ml.